Persepsi Petani dalam Penggunaan Teknologi Pengolahan Kopi Robusta Sistem Olah Madu pada Subak Abian di Desa Belatungan Kecamatan Pupuan - Desak Gede Karlina Satwiva Wijaya; Djoko Soejono (UNEJ e-Proceeding, 2018)
Robusta coffee is a potential commodity developed by the farming community in Belatungan, Pupuan. The development of Pupuan Robusta coffee is carried out continuously both by the government and the farmers as to maintain the quality of the processing technology on honey processed robusta ceffee. This study aimed to find out the farmers’ perceptions towards the innovation of the processing technology on honey processed robusta coffee. The study was conducted in Belatungan, Pupuan with a purposive method. Purposive sampling method with a certain criteria was used select the informants. The methods of observation, interviews, documentation and focus group discussion were used to obtain the primary and secondary data. The data was analyzed by using Miles and Huberman methods. The results of the study showed that the perception generated by someone over something was influenced by several factors, namely internal and external factors. The internal factors that influenced the farmers’ perceptions towards the application of processing technology on honey processed robusta ceffee were affected by its selling price which is more expensive, the short amount of processing time, the better quality and taste of robusta coffee, and the farmers’ expectation to maintain the processing technologi on honey processed robusta coffee. The external factors that influenced the farmers’ perceptions towards the application of the processing technology on honey processed robusta coffee were affected by several information of honey processed systems and by the easy procedures of it.